Analysis of Student Graduation at SMK Negeri 1 Stabat Using the C4.5 Algorithm - Sulis Sutiono; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to analyze the graduation rates of students at SMK Negeri 1 Stabat in the general subjects group using the C4.5 algorithm. Secondary data covering 717 students was collected and underwent a preprocessing stage to ensure accuracy. The modeling results indicate that the average score threshold for graduation is 73.823; of the 717 students, 709 are declared graduated and 8 did not pass. The use of the C4.5 algorithm has proven effective in providing insights into student graduation as well as generating decision tree visualizations that clarify the decision-making process. This study emphasizes the importance of applying data mining technology in education to enhance understanding of student learning outcomes.